SUSTAINABILITY STATUS OF MANGROVE ECOSYSTEM MANAGEMENT IN SEMBILANG NATIONAL PARK, BANYUASIN REGENCY, SOUTH SUMATERA PROVINCE - . Theresia; Mennofatria Boer; Niken T.M Pratiwi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
he utilization of mangrove in Sembilang National Park area has increased lately so that it is necessary to assess the sustainability of the mangrove ecosystem management in the region. The study was conducted in March-April 2015. The research location was in the National Park Sembilang, Banyuasin Regency, South Sumatra. The study used primary data and secondary data collections. The primary data were collected from direct observation of mangrove vegetation and via directs interviews of 86 respondents using purposive sampling method. The sustainability status and recommendations for management strategies were determined using Multi Dimensional Scaling (MDS) method approaching by RAPFISH (Rapid Assessment Technique for Fisheries).Current sustainabilitystatus of mangrove management in Sembilang National Park, Banyuasin Regency, South Sumatra was "less sustainable" with multidimensional sustainability index of 49.81. Priority attributes that need to be fixed in order to improve the status of sustainable management of mangrove ecosystems in the region were area changes, local knowledge, conflict of interest, and local wisdom. Alternative strategy priority for mangrove ecosystem management in the region was the empowerment of local community for sustainable mangrove utilization. Keywords: sembilang national park, RAPMANGROVE, mangrove ecosystem management